Genetic dissection of the pre-eclampsia susceptibility locus on chromosome 2q22 reveals shared novel risk factors for cardiovascular disease - Johnson, M.; Brennecke, S.; East, C.; Dyer, T.; Roten, L.; Proffitt, J.; Melton, P.; Fenstad, M.; Aalto-Viljakainen, T.; Mäkikallio, K.; Heinonen, S.; Kajantie, E.; et al. (2013)
Pre-eclampsia is an idiopathic pregnancy disorder promoting morbidity and mortality to both mother and child. Delivery of the fetus is the only means to resolve severe symptoms. Women with pre-eclamptic pregnancies demonstrate increased risk for later life cardiovascular disease (CVD) and good evidence suggests these two syndromes share several risk factors and pathophysiological mechanisms. To elucidate the genetic architecture of pre-eclampsia we have dissected our chromosome 2q22 susceptibility locus in an extended Australian and New Zealand familial cohort. Positional candidate genes were prioritized for exon-centric sequencing using bioinformatics, SNPing, transcriptional profiling and QTL-walking. In total, we interrogated 1598 variants from 52 genes. Four independent SNP associations satisfied our gene-centric multiple testing correction criteria: a missense LCT SNP (rs2322659, P = 0.0027), a synonymous LRP1B SNP (rs35821928, P = 0.0001), an UTR-3 RND3 SNP (rs115015150, P = 0.0024) and a missense GCA SNP (rs17783344, P = 0.0020). We replicated the LCT SNP association (P = 0.02) and observed a borderline association for the GCA SNP (P = 0.07) in an independent Australian case–control population. The LRP1B and RND3 SNP associations were not replicated in this same Australian singleton cohort. Moreover, these four SNP associations could not be replicated in two additional case–control populations from Norway and Finland. These four SNPs, however, exhibit pleiotropic effects with several quantitative CVD-related traits. Our results underscore the genetic complexity of pre-eclampsia and present novel empirical evidence of possible shared genetic mechanisms underlying both pre-eclampsia and other CVD-related risk factors.